Challenges faced by grandparents in taking care of their orphaned grandchildren in Chiredzi rural - Ngwenyenyi, Hardson (Midlands State University, 2017)
The study aimed to explore the challenges faced by grandmothers who are taking care of their orphaned grandchildren in Chiredzi rural. Relevant literature was discussed, as well as the role theory which formed the theoretical framework of the study. A qualitative paradigm was employed using explorative approach. Data was collected using in-depth interviews which was audio taped and was analysed using thematic analysis. The study targeted rural grandparents taking care of their orphaned grandchildren and purposive sampling was used to select 12 grandparents. The researcher observed ethics which included informed consent, anonymity, confidentiality and privacy. Major findings of the study showed that grandparents taking care of their orphaned grandchildren faced mental and problems, difficulties in social interactions, economic and physical challenges as well as financial challenges. The overall conclusion was that grandparents faced social, psychological, physical and economic challenges. Recommendations were made based on these findings and included that there is need for the government, non-governmental organisations relatives and the community to offer grandparents social, emotional, and economic support.